1997
DOI: 10.1042/cs0920593
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia, Hypocapnia and Spirometry at Altitude

Abstract: 1. Both hypoxia and hypocapnia can cause broncho-constriction in humans, and this could have a bearing on performance at high altitude or contribute to altitude sickness. We studied the relationship between spirometry, arterial oxygen saturation and end-tidal carbon dioxide (ETCO2) concentration in a group of healthy lowland adults during a stay at high altitude, and then evaluated the response to supplementary oxygen and administration of a beta 2 agonist. 2. We collected spirometric data from 51 members of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
3
15
0
4
Order By: Relevance
“…On returning to Base Camp after 6days, or more, climbing at 5000m or higher, the median A M S score was 0 (range 0-5), mean oxygen saturation 83.4% (range 76-90%) and mean capillary carbon dioxide tension 3.33 kPa (range 2.51-4.15 kPa). FEVI and PEF were a mean (95% confidence intervals) 4% (1.7-6.3%) and 26.4% (21.9-30.9%) higher than at sea level, similar to the results of a parallel study undertaken during the expedition [14]. The general linear model showed that although a higher AMS score on arrival at 5300m was associated with a greater reduction in cough threshold (F = 6.52, P < O.OOl), overall the reduction in cough threshold between sea level and arrival at 5300 m was not statistically significant.…”
Section: Citric Acid Cough Challenge (Figs 1-3)supporting
confidence: 73%
“…On returning to Base Camp after 6days, or more, climbing at 5000m or higher, the median A M S score was 0 (range 0-5), mean oxygen saturation 83.4% (range 76-90%) and mean capillary carbon dioxide tension 3.33 kPa (range 2.51-4.15 kPa). FEVI and PEF were a mean (95% confidence intervals) 4% (1.7-6.3%) and 26.4% (21.9-30.9%) higher than at sea level, similar to the results of a parallel study undertaken during the expedition [14]. The general linear model showed that although a higher AMS score on arrival at 5300m was associated with a greater reduction in cough threshold (F = 6.52, P < O.OOl), overall the reduction in cough threshold between sea level and arrival at 5300 m was not statistically significant.…”
Section: Citric Acid Cough Challenge (Figs 1-3)supporting
confidence: 73%
“…In accordance to previous observations, there was no correlation between the magnitude and direction of changes in FEF 25-75 and arterial oxygen saturation (Mason et al 2000;Pollard et al 1997). The individual variability may be explained by the magnitude of bronchoconstriction versus bronchodilation triggered by the ascent to altitude as well as the hypoxia or hypobaria-induced effect on lung fluid accumulation and clearance.…”
Section: Discussionsupporting
confidence: 92%
“…P revious investigations reported reduced forced vital capacity (FVC) [1][2][3][4][5][6][7][8][9][10][11][12] and reduced forced expiratory volume in 1 s (FEV1) [3,7,9,10,12], as well as increased closing volume (CV) [4,12,13], during the first days after ascent to altitudes of 2,800-5,300 m. These findings were interpreted as being consistent with pulmonary interstitial fluid accumulation or subclinical high-altitude pulmonary oedema (HAPE). However, there are several other factors that could also account for or contribute to the observed changes.…”
mentioning
confidence: 64%